Autosomal recessive hypotrichosis simplex with woolly hair: a report of a new family - Khalid Mohammad al Aboud; Daifullah Al Aboud (PAGEPress Publications, 2011)
Autosomal recessive hypotrichosis simplex with woolly hair is a rare dermatological disorder, characterized by sparse hair and tightly curled hair. We report on a new family affected with this disorder which has not previously been reported. In this family, 2 siblings were affected. We believe that the disorder is not rare, but is possibly misdiagnosed, and hence underreported.